Pelatihan Visual Story Telling sebagai Pengembangan Potensi Diri dan Kemandirian Siswa Tuna Rungu SLB YKK Kabupaten Pacitan - Unik Dian Cahyawati; Purwastya Pratmajaya Adi Lukistyawan; Agus Heru Setiawan; Johan Ies Wahyudi; Setyo Tohari Caturiyanto (Institut Seni Indonesia Surakarta, 2022)
The storytelling method is one method that influences student learning. With storytelling, students can make a mind map of the information they get and the ideas they want to convey. Students with special needs (deaf) need their method of storytelling. The PKM Photography Study Program from ISI Surakarta conducted photography training as a storytelling medium for students attending YKK Pacitan Elementary School, East Java. Through photo media, deaf students can easily convey ideas and assist in teaching and learning. In addition, this training improves students’ photography ability using DSLR and smartphone cameras. Students participating in photography training as a storytelling medium demonstrate their ability to take pictures of objects and write descriptions as a whole storytelling unit summarized in a photo catalog containing the works of all photography training participants as storytelling.